Gestão ambiental municipal: competência normativa do município aplicada a proposta de COMDEMA para o município de Luiz Antônio - SP - Grando, Francelino Lamy de Miranda (1999)
Due to the Brazilian Constitution from 1.988, the Municipalities were born as beings integrating the Brazilian Federation, with the States and the Union itself, setting a new standard for Constitucional Law studies. It depends on investigating the whole new borders for the Municipalities competency on editing and applicating the environmental law to get Knowing of the role the mayor, the local legislators and the citizens may play on acting for the purposes established on Art. 225 of the refered Magna Carta. Upon studies developped at the Country of Luiz Antonio, in the hinterland of Sao Paulo State, by senior and junior researchersfrom Sao Carlos Federal University altogether with elected locals, a proposal was reached consubstanciated in a draft of a proposed to be COMDEMA's Bill, standing COMDEMA for Local Council for Environmental Protection.